IMPLEMENTING GUESSING MEANING FROM CONTEXT PROCEDURE FOR VOCABULARY LEARNING IN JUNIOR HIGH SCHOOL IN INDONESIA - Dyah Ayu Kusuma Wardani; Ouda Teda Ena (Journal of English Education, 2019)
AbstractVocabulary learning often implies that there is no other way of learning than to memorize the words. This research showed that guessing meaning from context procedure can accommodate students in learning new vocabulary items. Since students were not equipped with a dictionary all of the time, it is essential to seek for an alternative in learning vocabulary. One of the alternative techniques in vocabulary learning was guessing meaning from context. The purpose of the study was to investigate the implementation of the guessing the meaning from the context in junior high schools in Yogyakarta. The research participants of this study were 30 students from different classes from a junior high school in Yogyakarta, Indonesia. The researcher conducted a pre-test at the beginning and a post-test at the end of the research. The result of the pre-test and post-test showed that there was an increase of students’ vocabulary mastery. The questionnaire was used to confirm the result of pre-test and post-test comparison. The result of the questionnaire showed that guessing meaning from context procedure was helpful for the students to understand word meaning.